2008
DOI: 10.1039/b713768k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of molecular glasses and the aggregation in solutions for lanthanum(iii), calcium(ii), and yttrium(iii) complexes of octanoyl-dl-alaninate

Abstract: Octanoylalaninato-metal (metal = calcium(II), yttrium(III), lanthanum(III), and zinc(II)) complexes were prepared and the first three metal complexes were found to readily form transparent and stable molecular glasses from methanol and chloroform solutions. The process of glass formation from solution was studied in detail. The effect of the central metal ions on the formation of glassy states was remarkable: the lanthanum and calcium complexes assumed glassy or crystalline states depending on the isolation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The remarkable difference in the properties between the hexyl and 2-ethylhexyl complexes was clarified for complexes with PF À 6 and NO À 3 counter anions, respectively. That study has been performed as one of those on metallosurfactants which sometimes showed unique aggregation states such as molecular glasses and liquid crystalline glasses [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable difference in the properties between the hexyl and 2-ethylhexyl complexes was clarified for complexes with PF À 6 and NO À 3 counter anions, respectively. That study has been performed as one of those on metallosurfactants which sometimes showed unique aggregation states such as molecular glasses and liquid crystalline glasses [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…2 θ =20° for all praseodymium(III) complexes indicates in‐plane disorder (i. e. disorder in alkyl‐chains). It originates from the disordered methylene‐methylene interaction [6] . This amorphous peak highlights the glassy state of the praseodymium(III) complexes.…”
Section: Resultsmentioning
confidence: 93%
“…The organo‐lanthanide complexes, in particular, have attracted organic chemists. In recent years, the octanoyl‐aminocarboxylates complexes of lanthanum(III), [6] magnesium(II), calcium(II), [7] yttrium(III), [8] europium(III), [9] and terbium(III) [10] have been synthesized, and their optical performance was verified through experiments. Usually, studies of optical properties of rare earth metal complexes focus on europium and terbium ions, and little on the praseodymium(III) complex.…”
Section: Introductionmentioning
confidence: 99%
“…SAXS profiles are usually expected to provide information on supramolecular structures in solid state [8]. Fig.…”
Section: Resultsmentioning
confidence: 99%